KEBIJAKAN HUKUM DAERAH TENTANG PENGELOLAAN PARKIR: PROBLEMATIKA DAN SOLUSINYA DI KOTA-KOTA BESAR - Samad, Izzan Firizqi Abdul; Wahyudin, Asep; Ramdhani, Fahmi Ali (Innovative: Journal Of Social Science Research, 2025)
Parking management falls under the authority of local governments in maintaining public order and transportation. In major cities, the increasing number of motor vehicles has led to various parking-related issues, such as illegal parking, unauthorized charges, and inefficient space utilization. Local governments, through legal policies—both regional regulations and their derivatives—seek to manage the parking sector to support traffic flow and enhance local revenue (PAD). However, practical challenges persist, including weak law enforcement, poor inter-agency coordination, and low public participation. This study aims to analyze local legal policies in parking management, identify prevailing problems, and propose legal and participatory solutions. Using a normative juridical and qualitative approach in several major Indonesian cities, this study finds that policy effectiveness depends greatly on the clarity of regulations, consistency of implementation, and robustness of monitoring. Thus, policy reform, improved administrative integrity, and community involvement are essential to ensure a fair, efficient, and sustainable parking management system.